2021
DOI: 10.1002/onco.13816
|View full text |Cite
|
Sign up to set email alerts
|

Hepatectomy Followed by Adjuvant Chemotherapy with 3-Month Capecitabine Plus Oxaliplatin for Colorectal Cancer Liver Metastases

Abstract: Three-month adjuvant capecitabine plus oxaliplatin in combination (CAPOX) appeared to reduce recurrence, with mild toxicity in postcurative resection of colorectal cancer liver metastases (CLM).• Recurrence in patients who underwent the 3-month adjuvant CAPOX after resection of CLM was most commonly at extrahepatic sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The benefit of oxaliplatin-based chemotherapy was suggested also by Sakamoto et al [ 42 ] in a small study of 24 patients treated with FOLFOX4 or modified FOLFOX6 along with a single-arm phase II study by Satake et al [ 35 ] that investigated the efficacy of CAPOX in 28 patients. The favorable role of FOLFOX and oxaliplatin plus 5-FU was proved by Kim et al [ 44 ] in a study with sixty patients that were compared with historical controls.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The benefit of oxaliplatin-based chemotherapy was suggested also by Sakamoto et al [ 42 ] in a small study of 24 patients treated with FOLFOX4 or modified FOLFOX6 along with a single-arm phase II study by Satake et al [ 35 ] that investigated the efficacy of CAPOX in 28 patients. The favorable role of FOLFOX and oxaliplatin plus 5-FU was proved by Kim et al [ 44 ] in a study with sixty patients that were compared with historical controls.…”
Section: Resultsmentioning
confidence: 88%
“…In the study of Satake et al [ 35 ], among 28 participants, 20 (71.4%, 95% CI: 53.6–89.3%) were able to complete the protocol treatment. Capecitabine was reduced in 10 (36%) and discontinued in 5 subjects (19%), whereas oxaliplatin dose reduction was reported in eight cases (29%) and discontinued in eight subjects (29%).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, although it was a single-arm study, Satake et al reported the benefits of 3 monthsʼ CAPOX treatment as adjuvant therapy after resection of liver metastases, with lower neurotoxicity and higher 5-year survival rate of 87% 14) . It may be acceptable to use adjuvant chemotherapy with fewer side effects in selected patients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, about 80% of patients are affected by unresectable CRLM, due to bilobar multiple liver metastases and/or extrahepatic disease. Nowadays, systemic chemotherapy regimens [ 64 , 76 , 79 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ] are proposed to convert patients with initially unresectable CRLM to obtaining and improving long-term surgical and oncological outcomes [ 23 , 82 , 90 , 91 , 92 , 93 ]. Nevertheless, some patients will progress during neoadjuvant chemotherapy with a debated role of liver resection in this subgroup.…”
Section: Survivalmentioning
confidence: 99%